sebuah Efektivitas Kejahatan dan Hukuman dalam Manajemen Lembaga Pemasyarakatan: Manajemen Lembaga Pemasyarakatan - Heigel Nobel Kurniadi Pasaribu; Rachel Yohanna Zefanya Meliala; Kezia Jerin Gandasuli; Giosia Hasian Situmorang (GEVANGENEN Jurnal Pemasyarakatan, 2026)
This article re-examines Indonesia’s penal system by highlighting the gap between its  formal  objectives  and  the  actual  conditions  within  correctional  facilities. Research   indicates  that   the  penal  approach  remains  heavily  centered  on imprisonment, resulting in chronic overcrowding, limited rehabilitation efforts, and diminished corrective outcomes. The fulfillment of inmates’ rights, including those of vulnerable groups such as women, is constrained by structural limitations and insufficient facilities. The effectiveness of correctional integration policies also remains uneven due to administrative barriers and assessment challenges. This article reviews the potential of restorative justice as a more proportional alternative capable of reducing pressure on correctional institutions. Through legal normative analysis,  it  proposes  reform  strategies  grounded  in humanistic principles, restorative orientation, and long-term effectiveness.